2019
DOI: 10.7717/peerj.6446
|View full text |Cite
|
Sign up to set email alerts
|

Everything you always wanted to know about gene flow in tropical landscapes (but were afraid to ask)

Abstract: The bulk of the world’s biodiversity is found in tropical regions, which are increasingly threatened by the human-led degradation of natural habitats. Yet, little is known about tropical biodiversity responses to habitat loss and fragmentation. Here we review all available literature assessing landscape effects on gene flow in tropical species, aiming to help unravel the factors underpinning functional connectivity in the tropics. We map and classify studies by focus species, the molecular markers employed, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Yang’s genetic relatedness between pairs of individuals (Yang et al, 2010) was used as a proxy for recent gene flow, given that it represents the number of common ancestors in the recent past (Wang, 2017). Although relatedness is not a direct measure of gene flow, it has been widely used to describe genetic connectivity among individuals (Storfer et al, 2010; Balkenhol et al, 2016; Monteiro et al, 2019) and a recent simulation study showed that it is among the most accurate individual-based genetic distance metric for landscape genetic studies (Shirk et al, 2017). Resistance to gene flow due to mining was modeled using land cover maps for different years (2016, 2014, 2011, and 1979) containing only the major land cover classes of our study region: Montane savanna (Canga), forest (evergreen forest), and mine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang’s genetic relatedness between pairs of individuals (Yang et al, 2010) was used as a proxy for recent gene flow, given that it represents the number of common ancestors in the recent past (Wang, 2017). Although relatedness is not a direct measure of gene flow, it has been widely used to describe genetic connectivity among individuals (Storfer et al, 2010; Balkenhol et al, 2016; Monteiro et al, 2019) and a recent simulation study showed that it is among the most accurate individual-based genetic distance metric for landscape genetic studies (Shirk et al, 2017). Resistance to gene flow due to mining was modeled using land cover maps for different years (2016, 2014, 2011, and 1979) containing only the major land cover classes of our study region: Montane savanna (Canga), forest (evergreen forest), and mine.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of ample evidence showing that habitat loss has large, consistently negative effects on biodiversity (Fahrig, 2003), very few studies have assessed the consequences of habitat amount on genetic variation (DiLeo and Wagner, 2016; Monteiro et al, 2019). Habitat loss can potentially impact the demographics of natural populations, reducing population size, gene flow, and genetic diversity, and thereby increasing inbreeding and extinction risk (Allendorf et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses project genetic variation into unsampled locations for which data on the driver are available, using the driver as a surrogate of genetic variation (Wasserman et al ., 2012; Hanson et al ., 2017). This has practical utility for highlighting migration corridors to limit genetic erosion (DiLeo & Wagner, 2016; Monteiro et al ., 2019), identifying priority conservation areas aimed at protecting within‐species genetic composition [e.g. conservation planning (Paz‐Vinas et al ., 2018; Hanson et al ., 2020)], or modeling population vulnerability and changes in adaptive capacity due to environmental change (Fitzpatrick & Keller, 2015; Martins et al ., 2018; Razgour et al ., 2018; Vranken et al ., 2021).…”
Section: Operationalizing Ebvs: From Single Studies To Global Usementioning
confidence: 99%
“…Yang's genetic relatedness between pairs of individuals (Yang et al, 2010) was used as a proxy for recent gene flow, given that it represents the number of common ancestors in the recent past (Wang, 2017). Although relatedness is not a direct measure of gene flow, it has been widely used to describe genetic connectivity among individuals (Balkenhol et al, 2016;Monteiro et al, 2019;Storfer et al, 2010) and a recent simulation study showed that it is among the most accurate individual-based genetic distance metric for landscape genetic studies (Shirk et al, 2017). Resistance to gene flow due to mining was modeled using land cover maps for different years (2016, 2014, 2011 and 1979) containing only the major land cover classes of our study region: Montane Savanna (Canga), Forest (evergreen forest) and Mine.…”
Section: Gene Flowmentioning
confidence: 99%